Study on the Ground Fissure Development Law of Coal Mining Based on UAV Photogrammetry and the Particle Flow Theory - Zhang, Yanjun; Kong, Jiayuan; Long, Sifang; Zhu, Yuanhao; Zhu, Wenxin; Wu, Tianhui (Frontiers in Environmental Science, 2022)
Ground fissures caused by coal mining subsidence are easy to result in secondary geological disasters and destroy the ecological environment, which threaten the safety of human life and property. The traditional monitoring method such as manual measurement and satellite monitoring has its own disadvantages. Therefore, it is necessary to develop new rapid monitoring technology of ground fissures and study its development law. In this paper, we analyzed the distribution characteristics of ground fissures based on the low-altitude UAV remote sensing images and combined with field investigation as validation. And we introduced the particle flow theory particle flow theory to study the development law of ground fissures. The study area in this paper is the surface of 8092 working face in a mine in Ordos City. Results showed the accuracy rate of ground fissures based on visual interpretation of UAV images was 95 %. The ground fissures were mainly distributed near the stopping line and the groove of the working face. The plane forms of ground fissures were mainly two types: linear type and arc type and the location relationship can be divided into parallel type and bifurcation type. The forms of ground fissures were tensile type and step type. Whether the upper and lower parts of the key strata were broken at the same time is the root cause of tensile ground fissures and step ground fissures. The stability of the overlying strata had a significant influence on the change of abutment pressure above the goaf. The process of surface movement and deformation can be divided into three stages: tensile failure of slope bottom—traction failure of slope body—sliding failure of slope top. In addition, the zero point of the maximum surface subsidence value and the horizontal movement value were not in the center of the goaf. And due to the horizontal slip of downhill direction of the horizontal movement on surface, the value of downhill direction subsidence was zero. In conclusion, the research results can provide useful reference for the rapid monitoring of geological disasters caused by coal mining subsidence and the application of particle flow theory.